Delay of gratification training for children: Cues from 'tarbiyyatul aulaad' - Elias, Nadiyah; Awang, Amir; Mohamed, Mahmood Nazar (2004)
Studies have shown that children with high level of ability to delay gratification tend to succeed more in social and academic life.Delay of gratification has been recognized as a component of emotional intelligence. Researchers have also linked many personal problem to lack of emotional intelligence, specifically the lack of ability to delay gratification.Western researchers have attempted to search for effective strategies to teach children how to raise their ability to delay gratification.7% article looks at the Islamic recommendations of socializing children to identify traditiona1 methods of training children to delay gratification.